Microclimate of the Natural History Museum, Vienna - Peter Brimblecombe; Alexander Bibl; Christian Fischer; Helmut Pristacz; Pascal Querner (Heritage)
Climate change increases the importance of maintaining environmental conditions suitable for preventive conservation within museums. The microclimates at the Natural History Museum of Vienna, a large national collection housed within a classical building, were studied using >200 data loggers placed from mid 2021 to provide thermo-hygrometric measurements at 15 min intervals. Daily mean temperatures showed exhibition halls typically had the warmest rooms. This was due to the heating in winter and open windows on summer days. The halls can become even hotter than the outside temperature. In winter, most areas of the museum were very dry, as heating lowered the relative humidity, typically to 25–35% for the coldest season. Opening hours imposed daily and weekly cycles on the internal climate. There was little difference between sunny and shaded parts of the building or adjacent offices, corridors and depots. Similarly, the microclimate at the floor resembled that of the room air some ~2 m above. Mechanically controlled microclimates in cold storage areas maintained 10 °C and relative humidity ~50%, but this had become increasingly difficult in hot summers. While there was little apparent damage to the collection, at times, the museum had an extreme indoor climate: very hot in the summer and dry in the winter.